Happiness at Work Affects the Performance of Educational Personnel in Secondary Schools, District 1 in Bangkok - Yamkgathok, Noppamas; Siriwong, Thongfu; Thungwa , Sompon; Thungwha, Laksamee (Journal of Modern Learning Development, 2022)
The purpose of this research was to study happiness at work of educational personnel of secondary schools, District 1 in Bangkok. To study the performance of educational personnel. To compare the performance classified by personal factors of educational personnel. to study the happiness at work affects the efficiency of work of educational personnel. The results showed that Most of them were The average score of overall happiness at work was at the highest level, with a mean of 4.56 standard deviation of 0.33. The mean score on the performance of educational personnel of secondary schools in District 1 in Bangkok. Overall, it was at the highest level, with a mean of 4.54, a standard deviation of 0.44. Work happiness affects the performance of educational personnel of secondary schools, District 1 in Bangkok. It was found that all aspects of work happiness affected work efficiency at a statistically significant level of 0.05 by working age. (F=23.911), average monthly income (F=15.072), marital status (F=9.420), job position (F=5.708), education level (F=4.632), age range (F=3.660), and gender (t=6.820). Affect the performance of educational personnel of secondary schools, District 1 in Bangkok. Happiness at work affecting the performance of educational personnel of secondary schools, District 1 in Bangkok with multiple regression analysis at the statistical significance level of 0.05, it was found that relationship (Beta=.692), love at work (Beta=.132), job success (Beta=.129) and acceptance (Beta=-.033). It had a positive effect on the performance of educational personnel in Secondary School District 1 in Bangkok, at a statistically significant level, p-value < 0.05 and can jointly explain 69.7 percent of the variance in the performance of educational personnel of secondary schools in District 1 in Bangkok. The remaining 30.3% due to the influence of other variables.The part of being accepted there was no effect on the performance of educational personnel in Secondary School District 1 in Bangkok. Multiple correlation coefficient (R = .835), adjusted predictive efficiency value (Adj. R2.692) (F=126.661), prediction error (S.E=.243).